Environment Performance Index Assessment on Food Production: A Case Study in Indonesia - Indah Apriliana Sari Wulandari; Hana Catur Wahyuni; Inggit Mardiyah; Nur Ravita Hanun (Jurnal Teknik Industri, 2022)
Green Productivity (GP) is a strategy to increase production output while protecting the environment. The application of GP is a tool to evaluate the quality of the environment. For instance, an industry of crispy fried chicken drains the chicken's wash water, pours cooking oil, and slurries down the drain. It will diminish water quality. This research aims to assess Environment Performance Index (EPI) and prevent environmental damage by creating crispy chicken. The initial step must be identifying waste, creating a material balance diagram, calculating EPI and productivity, and proposing alternatives. This research indicates that pollution levels in this industry are extremely high. Environmental Service testing of production wastewater revealed BOD values of 769mg/l, COD values of 1699mg/l, TSS values of 2536mg/l, and an EPI Index of -31,05 exceed government standards. The result indicates that production enhancements must continue. In addition, this research generated some waste prevention alternatives, such as constructing a grease trap.